ADAPTASI UMAT HINDU DI DESA TAGAGIRI TAMA JAYA KECAMATAN PELANGIRAN KABUPATEN INDRAGIRI HILIR PROVINSI RIAU - Wayan Sepiyana; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research was about the Adaptation of Hindus people in Tagagiri Tama Jaya Village. The research method used a descriptive qualitative approach. How to determine informants by purposive sampling. The study subjects were five persons, they were three as key informants and two as informants. The results of this study identified that the adaptation ability of Hindus people went well. First, adaptation was done through participation in social, cultural and religious activities. Social activities include mutual cooperation activities, rewang, attending a party celebration. Cultural activities were carried out by performing lumping horse art performances. Religious activities include attending the anniversary of the Prophet's Birthday, Christmas Celebration. Second, adaptation went well because Hindus people succeed in understanding the realm or environment in which they live. By indirectly understanding the domains, Hindus people succeed in forming a social network among the people in the area. Third, there were sources of capital owned by Hindus people, include social, economic, cultural and symbolic capital. Owned social capital based on a long process of socialization and social interaction, friendship, and good contact and communication among citizens. For economic capital, they have coconut plantations, vacant fields or fields. For cultural capital they were displaying Hindu religious symbols, took the initiative to establish a lumping horse group. For symbolic capital tey were gaining trust as the leader of the lumping horse group, and serving in the village administration as planning staff. Keywords : Hindus People Adaptation, Habitus, Domains, Source of Capital, Pierre Bourdieu